Exploring the fabrication and transfer mechanism of metallic nanostructures on carbon nanomembranes via focused electron beam induced processing - Preischl, Christian; Le, Linh Hoang; Bilgilisoy, Elif; Gölzhäuser, Armin; Marbach, Hubertus (Beilstein Journal of Nanotechnology, 2021)
Focused electron beam-induced processing is a versatile method for the fabrication of metallic nanostructures with arbitrary shape, in particular, on top of two-dimensional (2D) organic materials, such as self-assembled monolayers (SAMs). Two methods, namely electron beam-induced deposition (EBID) and electron beam-induced surface activation (EBISA) are studied with the precursors Fe(CO)5 and Co(CO)3NO on SAMs of 1,1′,4′,1′′-terphenyl-4-thiol (TPT). For Co(CO)3NO only EBID leads to deposits consisting of cobalt oxide. In the case of Fe(CO)5 EBID and EBISA yield deposits consisting of iron nanocrystals with high purity. Remarkably, the EBISA process exhibits a strong time dependence, which is analyzed in detail for different electron doses. This time dependence is a new phenomenon, which, to the best of our knowledge, was not reported before. The electron-induced cross-linking of the SAM caused by the cleavage of C–H bonds and the subsequent formation of new C–C bonds between neighboring molecules also seems to play a crucial role in the EBISA process. Previous studies showed that iron nanostructures fabricated on top of a cross-linked SAM on Au/mica can be transferred to solid substrates and grids without any changes, aside from oxidation. Here we demonstrate that iron as well as cobalt oxide structures on top of a cross-linked SAM on Ag/mica do change more significantly. The Fe(NO3)3 solution used for etching of the Ag layer also dissolves the cobalt oxide structures and causes dissolution and reduction of the iron structures. These results demonstrate that the fabrication of hybrids of metallic nanostructures onto organic 2D materials is an intrinsically complex procedure. The interactions among the metallic deposits, the substrate for the growth of the SAM, and the associated etching/dissolving agent need to be considered and further studied.
Keywords: 2D materials; carbon nanomembranes (CNMs); focused electron beam-induced processing; metallic nanostructures; self-assembled monolayers

(untitled) - Randolph, S. J.; Fowlkes, J. D.; Rack, P. D. (Crit. Rev. Solid State Mater. Sci., 2006)

(untitled) - van Dorp, W. F.; Hagen, C. W. (J. Appl. Phys., 2008)

(untitled) - Utke, I.; Hoffmann, P.; Melngailis, J. (J. Vac. Sci. Technol., B: Microelectron. Nanometer Struct.–Process., Meas., Phenom., 2008)

(untitled) - Botman, A.; Mulders, J. J. L.; Hagen, C. W. (Nanotechnology, 2009)

(untitled) - Huth, M.; Porrati, F.; Schwalb, C.; Winhold, M.; Sachser, R.; Dukic, M.; Adams, J.; Fantner, G. (Beilstein J. Nanotechnol., 2012)

(untitled) - Jesse, S.; Borisevich, A. Y.; Fowlkes, J. D.; Lupini, A. R.; Rack, P. D.; Unocic, R. R.; Sumpter, B. G.; Kalinin, S. V.; Belianinov, A.; Ovchinnikova, O. S. (ACS Nano, 2016)

(untitled) - Fowlkes, J. D.; Winkler, R.; Lewis, B. B.; Stanford, M. G.; Plank, H.; Rack, P. D. (ACS Nano, 2016)

(untitled) - Winkler, R.; Fowlkes, J. D.; Rack, P. D.; Plank, H. (J. Appl. Phys., 2019)

(untitled) - Mehendale, S.; Mulders, J. J. L.; Trompenaars, P. H. F. (Microelectron. Eng., 2015)

(untitled) - Walz, M.-M.; Vollnhals, F.; Schirmer, M.; Steinrück, H.-P.; Marbach, H. (Phys. Chem. Chem. Phys., 2011)

(untitled) - Marbach, H. (Appl. Phys. A: Mater. Sci. Process., 2014)

(untitled) - Walz, M.-M.; Schirmer, M.; Vollnhals, F.; Lukasczyk, T.; Steinrück, H.-P.; Marbach, H. (Angew. Chem., Int. Ed., 2010)

(untitled) - Muthukumar, K.; Jeschke, H. O.; Valentí, R.; Begun, E.; Schwenk, J.; Porrati, F.; Huth, M. (Beilstein J. Nanotechnol., 2012)

(untitled) - Vollnhals, F.; Wintrich, P.; Walz, M.-M.; Steinrück, H.-P.; Marbach, H. (Langmuir, 2013)

(untitled) - Drost, M.; Tu, F.; Vollnhals, F.; Szenti, I.; Kiss, J.; Marbach, H. (Small Methods, 2017)

(untitled) - Drost, M.; Tu, F.; Berger, L.; Preischl, C.; Zhou, W.; Gliemann, H.; Wöll, C.; Marbach, H. (ACS Nano, 2018)

(untitled) - Ahlenhoff, K.; Preischl, C.; Swiderek, P.; Marbach, H. (J. Phys. Chem. C, 2018)

(untitled) - Vollnhals, F.; Woolcot, T.; Walz, M.-M.; Seiler, S.; Steinrück, H.-P.; Thornton, G.; Marbach, H. (J. Phys. Chem. C, 2013)

(untitled) - Lee, J.; Zhang, Z.; Yates, J. T., Jr (Phys. Rev. B, 2009)

(untitled) - Vollnhals, F.; Drost, M.; Tu, F.; Carrasco, E.; Späth, A.; Fink, R. H.; Steinrück, H.-P.; Marbach, H. (Beilstein J. Nanotechnol., 2014)

(untitled) - Preischl, C.; Le, L. H.; Bilgilisoy, E.; Vollnhals, F.; Gölzhäuser, A.; Marbach, H. (Small, 2020)

(untitled) - Turchanin, A.; El-Desawy, M.; Gölzhäuser, A. (Appl. Phys. Lett., 2007)

(untitled) - Zhang, X.; Neumann, C.; Angelova, P.; Beyer, A.; Gölzhäuser, A. (Langmuir, 2014)

(untitled) - Geyer, W.; Stadler, V.; Eck, W.; Zharnikov, M.; Gölzhäuser, A.; Grunze, M. (Appl. Phys. Lett., 1999)

(untitled) - Nottbohm, C. T.; Beyer, A.; Sologubenko, A. S.; Ennen, I.; Hütten, A.; Rösner, H.; Eck, W.; Mayer, J.; Gölzhäuser, A. (Ultramicroscopy, 2008)

(untitled) - Angelova, P.; Vieker, H.; Weber, N.-E.; Matei, D.; Reimer, O.; Meier, I.; Kurasch, S.; Biskupek, J.; Lorbach, D.; Wunderlich, K.; Chen, L.; Terfort, A.; et al. (ACS Nano, 2013)

(untitled) - Turchanin, A.; Beyer, A.; Nottbohm, C. T.; Zhang, X.; Stosch, R.; Sologubenko, A.; Mayer, J.; Hinze, P.; Weimann, T.; Gölzhäuser, A. (Adv. Mater. (Weinheim, Ger.), 2009)

(untitled) - Dementyev, P.; Naberezhnyi, D.; Westphal, M.; Buck, M.; Gölzhäuser, A. (ChemPhysChem, 2020)

(untitled) - Neumann, C.; Szwed, M.; Frey, M.; Tang, Z.; Kozieł, K.; Cyganik, P.; Turchanin, A. (ACS Appl. Mater. Interfaces, 2019)

(untitled) - Plank, H.; Smith, D. A.; Haber, T.; Rack, P. D.; Hofer, F. (ACS Nano, 2012)

(untitled) - Walz, M.-M.; Vollnhals, F.; Rietzler, F.; Schirmer, M.; Steinrück, H.-P.; Marbach, H. (Appl. Phys. Lett., 2012)

(untitled) - Turchanin, A.; Käfer, D.; El-Desawy, M.; Wöll, C.; Witte, G.; Gölzhäuser, A. (Langmuir, 2009)

Corrosion for everybody - Groysman, A. (Springer Science & Business Media, 2009)

(untitled) - Shawrav, M. M.; Taus, P.; Wanzenboeck, H. D.; Schinnerl, M.; Stöger-Pollach, M.; Schwarz, S.; Steiger-Thirsfeld, A.; Bertagnolli, E. (Sci. Rep., 2016)

(untitled) - Berger, L.; Madajska, K.; Szymanska, I. B.; Höflich, K.; Polyakov, M. N.; Jurczyk, J.; Guerra-Nuñez, C.; Utke, I. (Beilstein J. Nanotechnol., 2018)

(untitled) - Friedli, V.; Utke, I. (J. Phys. D: Appl. Phys., 2009)

(untitled) - Schirmer, M.; Walz, M.-M.; Vollnhals, F.; Lukasczyk, T.; Sandmann, A.; Chen, C.; Steinrück, H.-P.; Marbach, H. (Nanotechnology, 2011)